Serum Intact Parathyroid Hormone Level is Inversely Correlated with Glycated Haemoglobin in Diabetic Chronic Kidney Disease Stages 3-5 Predialysis Patients - Ul Haque, Wasim Md Mohosin; Rahim, Muhammad Abdur; Mitra, Palash; Samad, Tabassum; Habib, Samira Humaira; Iqbal, Sarwar (BIRDEM Medical Journal, 2017)
Introduction: Diabetes mellitus (DM) is one of the leading causes of chronic kidney disease (CKD). Management of chronic kidney disease-mineral and bone disorder (CKD-MBD) is an integral component of CKD management; serum intact parathyroid hormone (iPTH) level is the key target. This study was designed to evaluate the relationship between glycated haemoglobin (HbAlc) and iPTH in diabetic CKD stages 3-5 patients not yet on dialysis. Methods: This cross-sectional study was conducted in BIRDEM General Hospital, Dhaka, Bangladesh from January 2013 to December 2014. Diabetic patients suffering from CKD stages 3-5, who were not on dialysis, were consecutively and purposively included in this study. Along with base-line characteristics, clinical and laboratory data including HbAlc and iPTH levels were recorded for all patients. Data were analyzed by using SPSS version 20.0 and Pearsons correlation test was applied to evaluate the relationship between HbAlc and iPTH. Results: Total patients were 306, including 166 (54.2%) males. Mean age was 56.5±11.3 years. Mean duration of DM and CKD were 12.8±7.6 and 2.9±1.7 years respectively. Among the study population, 49 (16.0%) were in CKD stage 3, 90 (29.4%) in CKD stage 4 and rest 167 (54.6%) in CKD stage 5. Mean HbAlc (%), serum creatinine (mg/dl), urea (mg/dl), calcium (mg/dl), phosphate (mg/dl), alkaline phosphatase (U/L) and iPTH (pg/ml) were 7.77±2.14, 6.8±3.0, 141.1±75.7, 8.1±1.2, 5.2±1.9,164.1±135.3 and 229.7±151.2 respectively. Mean HbAlc (%) and iPTH (pg/ml) in CKD stages 3, 4 and 5 were 8.36±1.59 and 171.7±127.9, 7.99±1.92 and 179.5±131.4, and 7.77±2.14 and 273.8±119.2 respectively. On correlation analysis, HbAlc had a significant negative correlation with iPTH (r=-0.002). Conclusion: The results of current study showed that most diabetic CKD stages 3-5 predialysis patients had poor glycaemic control and HbAlc had negative correlation with iPTH. As iPTH level is influenced by presence and control of DM, the targets of iPTH in CKD stages 3-5 in general, as recommended in existing guidelines, may not be appropriate in diabetic CKD patients and this issue merits further investigation. Birdem Med J 2017; 7(2): 110-113